2015
DOI: 10.3389/fmicb.2015.00492
|View full text |Cite
|
Sign up to set email alerts
|

Methanogenic archaea and sulfate reducing bacteria co-cultured on acetate: teamwork or coexistence?

Abstract: Acetate is a major product of fermentation processes and an important substrate for sulfate reducing bacteria and methanogenic archaea. Most studies on acetate catabolism by sulfate reducers and methanogens have used pure cultures. Less is known about acetate conversion by mixed pure cultures and the interactions between both groups. We tested interspecies hydrogen transfer and coexistence between marine methanogens and sulfate reducers using mixed pure cultures of two types of microorganisms. First, Desulfovi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(66 citation statements)
references
References 61 publications
4
62
0
Order By: Relevance
“…It is possible that the population of Pyr ϩ cells in the aggregates is not biochemically homogeneous, with one subset of the population performing hydrogenotrophic methanogenesis and the second aceticlastic methanogenesis. It has been reported that these two reactions can be coordinated between two methanogenic strains (30). Since H 2 inhibits aceticlastic growth, in the cell aggregates, hydrogenotrophic methanogens would lower the H 2 partial pressure to a level that would allow aceticlastic methanogenesis to occur and therefore allow the organism to metabolize pyruvate.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the population of Pyr ϩ cells in the aggregates is not biochemically homogeneous, with one subset of the population performing hydrogenotrophic methanogenesis and the second aceticlastic methanogenesis. It has been reported that these two reactions can be coordinated between two methanogenic strains (30). Since H 2 inhibits aceticlastic growth, in the cell aggregates, hydrogenotrophic methanogens would lower the H 2 partial pressure to a level that would allow aceticlastic methanogenesis to occur and therefore allow the organism to metabolize pyruvate.…”
Section: Discussionmentioning
confidence: 99%
“…A similar study observed Desulfovibrio and Desulfomicrobium persisting in ethanol fed pilot-scale bioreactors, yet low levels of methanogens . These studies, as well 71 as others Ozuolmez et al, 2015;Paulo et al, 2015) highlight two important interactions in anaerobic settings; SRB competition with methanogenic archaea for substrates, and SRB reliance on the degradation production of fermentive acetogens. Both scenarios contribute to successful passive treatment systems for ARD, as they influence the livelihood of the primary metal-immobilizing agents, sulfate reducing bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…However, rarely in nature do individual microbial groups function alone; rather there exists a complex network of substrate sharing and/or competition between different bacterial guilds, often partitioned by distinct chemical or redox zones. SRB will coexist with multiple species, contending for carbon substrates with methanogens and homoacetogens, and often relying on the degradation products of amino acids, sugars, and long-chain fatty acids by fermentative bacteria Ozuolmez et al, 2015). Few studies have explored the interactions of SRB with other species and associated metalsulfide precipitation (Alexandrino et al, 2014;Zhang et al, 2016), thus a research gap exists in this context.…”
Section: Omic Approaches In Amd Studiesmentioning
confidence: 99%
“…However, a cooccurrence of sulfate reducing bacteria and methanogens was detected, indicating either that the abundance of organic matter allows the presence of these organisms by reducing substrate competition or that the detected methanogens are capable of using substrates that are not used by sulfate reducing bacteria. A recent article described the dynamics of hydrogen transfer between an acetoclastic methanogen and hydrogenotrophic microorganisms, grown in pure and mixed cultures, and the results suggest that these organisms coexist and do not compete in marine sediments [62]. …”
Section: Archaea In Marine and Freshwater Sedimentsmentioning
confidence: 99%